Overexpression of a phosphatidic acid phosphatase type 2 leads to an increase in triacylglycerol production in oleaginous Rhodococcus strains - Hernández, Martín Alejandro (2014)
Oleaginous Rhodococcus strains are able to accumulate large amounts of triacylglycerol (TAG). Phosphatidic acid phosphatase (PAP) enzyme catalyzes the dephosphorylation of phosphatidic acid (PA) to yield diacylglycerol (DAG), a key precursor for TAG biosynthesis. Studies to establish its role in lipid metabolism have been mainly focused in eukaryotes but not in bacteria. In this work, we identified and characterized a putative PAP type 2 (PAP2) encoded by the ro00075 gene in Rhodococcus jostii RHA1. Heterologous expression of ro00075 in Escherichia coli resulted in a fourfold increase in PAP activity and twofold in DAG content. The conditional deletion of ro00075 in RHA1 led to a decrease in the content of DAG and TAG, whereas its overexpression in both RHA1 and Rhodococcus opacus PD630 promoted an increase up to 10 to 15% by cellular dry weight in TAG content. On the other hand, expression of ro00075 in the nonoleaginous strain Rhodococcus fascians F7 promoted an increase in total fatty acid content up to 7% at the expense of free fatty acid (FFA), DAG, and TAG fractions. Moreover, coexpression of ro00075 / atf 2 genes resulted in a fourfold increase in total fatty acid content by a further increase of the FFA and TAG fractions. The results of this study suggest that ro00075 encodes for a PAP2 enzyme actively involved in TAG biosynthesis. Overexpression of this gene, as single one or with an atf gene, provides an alternative approach to increase the biosynthesis and accumulation of bacterial oils as a potential source of raw material for biofuel production.